2015
DOI: 10.1038/srep15871
|View full text |Cite|
|
Sign up to set email alerts
|

Plant-microbe rhizosphere interactions mediated by Rehmannia glutinosa root exudates under consecutive monoculture

Abstract: Under consecutive monoculture, the biomass and quality of Rehmannia glutinosa declines significantly. Consecutive monoculture of R. glutinosa in a four-year field trial led to significant growth inhibition. Most phenolic acids in root exudates had cumulative effects over time under sterile conditions, but these effects were not observed in the rhizosphere under monoculture conditions. It suggested soil microbes might be involved in the degradation and conversion of phenolic acids from the monocultured plants. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
141
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 116 publications
(148 citation statements)
references
References 41 publications
6
141
0
1
Order By: Relevance
“…W 12 (Wu et al 2015). Research has confirmed that F. oxysporum is the pathogenic pathogens of R. glutinosa disease (Li et al 2013) and that most strains of Pseudomonas showed antagonistic activity against F. oxysporum (Borah et al 2015;Chin-A-Woeng et al 2000;Srinivasan et al 2009).…”
Section: Discussionmentioning
confidence: 77%
“…W 12 (Wu et al 2015). Research has confirmed that F. oxysporum is the pathogenic pathogens of R. glutinosa disease (Li et al 2013) and that most strains of Pseudomonas showed antagonistic activity against F. oxysporum (Borah et al 2015;Chin-A-Woeng et al 2000;Srinivasan et al 2009).…”
Section: Discussionmentioning
confidence: 77%
“…The monocultured plots without microbial fertilizer treatment (NMF) were found to have the lowest pH ( Figure 3 ). Previous studies have shown that consecutive monoculture of many plants could lead to a significant decrease in soil pH (Meriles et al, 2009; Wu et al, 2015). Many pathogenic fungi including Fusarium spp.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of phenolic acids caused significant increases in the population of pathogenic microorganisms in plate cultures and field experiments Zhang et al 2016). Allelochemicals of root exudates mediated adverse chemotaxis of rhizospheric microbes (Wu et al 2015;Zhang et al 2013). The immune systems of R. glutinosa are activated and finally compromised due to continuous attack by a large number of proliferating pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Given these typical characteristics, R. glutinosa is an ideal material for studying the mechanism of formation of consecutive monoculture problems Wen et al 2002). Previous studies have indicated that some biotic and abiotic stress factors involved in the formation of consecutive monoculture problems in R. glutinosa (Tian et al 2017;Wu et al 2015). In consecutive monocultures of R. glutinosa, root exudates selectively attract pathogenic microbes, which colonize the root surface in consecutive monocultures of R. glutinosa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation